Family Well‐Being During the COVID‐19 Pandemic: The Risks of Financial Insecurity and Coping. (24th June 2022) - Gonzalez, Marybel R.; Brown, Sandra A.; Pelham, William E.; Bodison, Stefanie C.; McCabe, Connor; Baker, Fiona C.; Baskin‐Sommers, Arielle; Dick, Anthony Steven; Dowling, Gayathri J.; Gebreselassie, Sabrina; Guillaume, Mathieu; Marshall, Andrew T.; et al.
Abstract : During the COVID‐19 pandemic, families have experienced unprecedented financial and social disruptions. We studied the impact of preexisting psychosocial factors and pandemic‐related financial and social disruptions in relation to family well‐being among N  = 4091 adolescents and parents during early summer 2020, participating in the Adolescent Brain Cognitive Development SM Study. Poorer family well‐being was linked to prepandemic psychosocial and financial adversity and was associated with pandemic‐related material hardship and social disruptions to routines. Parental alcohol use increased risk for worsening of family relationships, while a greater endorsement of coping strategies was mainly associated with overall better family well‐being. Financial and mental health support may be critical for family well‐being during and after a widespread crisis, such as the COVID‐19 pandemic.